BAGAIMANA MEMANFAATKAN DAN MENGKOORDINASIKAN BUSINESS NETWORK RESOURCES UNTUK INTERNASIONALISASI PASAR? - Sunarko, Bambang; Suroso, Agus (Faculty of Economics and Business Universitas Jenderal Soedirman, 2012)
Globalization has strong influence on SMEs business and some see this phenomenon as an opportunity to expand. Improved technology and communications have made it easier for firms of all sizes and in various locations to do business with each other. More businesses today including SMEs are pursuit foreign market for the reason of business growth. Palm sugar is the main product of Banyumas Regency and its market coverage ranging from domestic to foreign market. This research is aimed to understand the process of internationalization, how the resources are should be organized to reach foreign market. Research strategy used is case study since its complexity of the phenomena. This case study of SMEs illustrate the process of market internationalization and provides useful insight for both government and SMEs which are intend to enter foreign markets.